No slow dusk : Maya urban development and decline at La Milpa, Belize - Hammond, Norman
The 1998 excavations at the Maya city of La Milpa have revealed important structures of the ruling élite, including several throne rooms, but also evidence for a sudden cessation of élite activity when the occupation was at its height. Extensive mapping suggests a population of some 46,000 over a short period in the 8th and 9th centuries AD.